Formulasi Pembuatan Jelly Powder Flavour Vanilla Meggunakan Gracilaria Sp Dengan Penambahan Karagenan - Seftiono, Hermawan; Hartanto, Adrian; Taufik, Moh. (JURNAL AGROINDUSTRI HALAL, 2025)
Jelly powder is a product that can be used as the main raw material in the manufacture of jelly drinks, jelly candy, jelly pudding, and others; the primary function of jelly powder is to improve the viscosity and strength of the gel in the product you want to make. In this research, Jelly powder used Gracilaria sp. as the main ingredient and carrageenan as a gelling agent in jelly products. Gracilaria sp. was chosen because it is relatively easy to cultivate and abundantly available in the sea. This research aimed to determine vanilla flavored jelly powder's formulation and analyze the sensory properties. The methods used in the sample extraction process are soaking, drying, bleaching, acidification, and grinding. The data obtained were then processed by one-way analysis of variance (ANOVA) at a 95% confidence level using Duncan's further test. The best formulation from the results of the organoleptic analysis is F3. This formulation has hedonic values for taste, aroma, texture, aftertaste, and overall, respectively, 3.52 ± 0.82, 3.18 ± 0.8, 3.9 ± 0.78, 3.73 ± 0.7, and 3.58 ± 0.31. This formulation showed good organoleptic values across all parameters, indicating its potential to be the best formula for producing jelly powder